Widespread Mislocalization of FUS Is Associated With Mitochondrial Abnormalities in Skeletal Muscle in Amyotrophic Lateral Sclerosis With FUS Mutations. Issue 3 (9th February 2022) - Yu, Meng; Zhao, Xutong; Wu, Wei; Wang, Qingqing; Liu, Jing; Zhang, Wei; Yuan, Yun; Hong, Daojun; Wang, Zhaoxia; Deng, Jianwen
Abstract: Mutations in the fused in sarcoma ( FUS ) gene have been reported to be the most common genetic cause of early-onset amyotrophic lateral sclerosis (ALS); cytoplasmic inclusions containing FUS protein are the predominant pathological feature. Recent studies indicated that mutant FUS impaired neuromuscular junctions and induced muscle intrinsic toxicity in cell and animal models. However, the role of FUS in muscle degeneration remains unclear. In this study, we investigated FUS protein distribution in skeletal muscle fibers in ALS-FUS. Our data show that cytoplasmic mislocalized FUS in the unaggregated form represented a remarkable pathological feature in affected muscle fibers in ALS-FUS. Additional studies found that cytoplasmic FUS colocalized with some mitochondria and was associated with mitochondrial swelling and disorganized cristae. RNA sequencing and quantitative real-time polymerase chain reaction analyses indicated downregulation of the key subunits of mitochondrial oxidative phosphorylation complexes in the affected skeletal muscle in ALS-FUS patients. Further immunoblot analysis showed increased levels of FUS, but decreased levels of Cox I (subunit of complex IV) in ALS-FUS patients compared with age-matched controls. This is the first demonstration of the close association of cytoplasmic mislocalized FUS with mitochondrial dysfunction in skeletal muscle, implicating the presence of a cell-autonomous mechanism in muscle degeneration in ALS.